Africa Region - Regional Environmental Information Management Program - Mastri, Lawrence (World Bank, Washington, DC, 2012)
The primary goal of the Regional Environmental Information Management Program (REIMP) was to improve planning and management of natural resources in the Congo Basin, with specific focus on biodiversity conservation, by providing the various stakeholders with appropriate information on the environment in response to the needs they identify. The project has five objectives: (i) ensure the circulation of environmental information and optimize benefits from existing initiatives; (ii) foster involvement of decision makers in environmental information use and facilitate sound land use planning in the Congo Basin; (iii) provide users (public and private sectors, non-governmental organizations (NGOs), sub regional, and international organizations) with environmental information meeting their demand; (iv) strengthen national capacities for environmental information management; and (v) implement a Regional Fund for Local Initiatives (REFLI).